The Most Important Thing You Need to Know About Meta-Analyses. - Moore, Randall F. (Psychiatric Times, 2022)
The article provides understanding of the most important information that clinicians need to know about meta-analyses. Topics discussed are dispersion of true effects of size and dispersion secondary to sampling error, equation for the prediction interval and its use in the practice of clinical medicine as well as in choosing among treatments, and distinction of prediction from confidence interval.